Qualification of Child Status from Unregistered Polygamous Marriage without Marriage Validation (Study of Religious Court Decisions from 2019-2022) - Yuliani Tarais; Hartini Hartini (Universitas Negeri Semarang, 2023)
This study aims to analyze the qualification of child status carried out by the Religious Court in cases of determining the origin of children in unregistered polygamous marriages that are not validated from 2019-2022. The second objective is to analyze the legal implications of the qualification of the child’s status. The research method used is normative juridical research, which is carried out by studying secondary data and conducting interviews. The collected data is analyzed qualitatively. The research results show that there are three qualifications of child status made by judges in the request for determining the origin of children from unregistered marriages without marriage validation, namely (1) determined as a legitimate child, (2) determined as a biological child, and (3) determined as a child of Applicant I (biological father) with Applicant II (Mother). The legal implications of this qualification are to provide different legal consequences for the rights of children, even if they originate from similar cases. The existence of different court rulings has an impact on the rights received by children from unregistered polygamous marriages that are not validated, on the one hand, it is seen as a form of legal discovery by judges, but on the other hand, it creates a disparity in decisions because it ignores the principle of similia similibus.